Pelaksanaan Pengolahan Sampah Pada Dinas Lingkungan Hidup dan Kebersihan Kota Palembang - Sutinah Andaryani; Ida Utami Dwikurniawati; Rusdi Rusdi (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2023)
This study aims to analyze the waste management carried out by DLHK Palembang City. This study was a qualitative descriptive research. In collecting the research data, the writer conducted observation and interview, literature study and documentation. The results showed that the waste reduction activities implemented by the Environment and Sanitation Service Palembang were the establishment of Garbage Bank and TPS 3R, providing socialization and technical guidance on waste management to community, issuing appeals, circulars and socialization on reducing plastic waste to retail entrepreneurs, using tumblers, and restrictions on using plastic bags. The amount of waste made in Palembang in 2020 was 426,390.66 tones, with waste reduction (19.79%) and waste management (76.69%), managed waste (96.49%) and unmanaged waste (3.51%). The waste composition was dominated by food waste. There were obstacles in waste management, where the Garbage Bank, TPS 3R, waste collectors did not operate due to crowd restrictions, reduced volume of segregated waste from waste sources, and lack of public awareness in waste segregation and the use of re-useable products